A Quantitative Assessment of the Implications of Including non-CO2 Emissions in the European ETS - Carlo Orecchia; Ramiro Parrado (Fondazione Eni Enrico Mattei (FEEM), 2013)
Although CO2 emissions stand for most of greenhouse gas (GHG) emissions, the contribution of mitigation efforts based on non-CO2 emissions is still a field that needs to be explored more thoroughly. Extending abatement opportunities to non-CO2 could reduce overall mitigation costs but it could also exert a negative pressure on agricultural output. This paper offers insights about the first effect while provides a preliminary discussion for the second. We investigate the role of non-CO2 GHGs in climate change mitigation in Europe using a computable general equilibrium (CGE) model. We develop a specific modelling framework extending the model with non-CO2 GHGs as an additional mitigation alternative. These modifications allow us to analyse the implications for the European Union (EU) of including non-CO2 GHG emissions in its cap and trade system. We distinguish two targets on all GHG emissions for 2020, a reduction by 20% and 30% with respect to 1990 levels. Within each reduction cap, we consider two mitigation opportunities by means of a carbon tax levied on: 1) CO2 emissions only, and 2) All GHGs emissions (both CO2 and non-CO2 GHG). Results show that a multi-gas mitigation policy would slightly decrease policy costs compared to the CO2 only alternative.
Keywords: Q5; Q58; 330; CGE; Greenhouse gas emissions; Cap-and-trade system; Agriculture; Non-CO2 emissions; European Union; Effort Sharing Decision